Transforming developing economies by shifting paradigms beyond natural resources. The fintech and social dynamics for sustainable mineral policy - Hasan, Mohammad Maruf; Hasan, Md Enamul; Ghosh, Tusher (Elsevier, 2024)
This study aims to develop a comparative analysis of fintech and social structure with the conventional drivers of economic growth and natural resource utilization to highlight their contribution to the SDGs-2030 transition. For this purpose, a dataset of the sub-Saharan African region was selected between 2010 and 2022. The advanced econometric FGLS method, along with other necessary forecasting parameters, was adopted for the empirical analysis. The observed outcomes confirmed that African economies are “resource dependent” and social factors integration following the “Socio-Technical Systems” theory. Furthermore, study outcomes confirmed the “institutional theory” of the positive impact of social structures on the sustainability process. Moreover, fintech infusion in the system proved “stakeholder theory” that digital-led-financial solutions facilitate stakeholders’ and influence sustainable mineral extraction and development. These outcomes suggest that social and unconventional factors emerged as highly significant features in this process. Thus, fintech and social factor integration offer a pathway to enhance financial inclusion in African economies, drive sustainable development, and integrate African mineral markets with the global economy. However, this requires rigorous efforts from public authorities, financial institutions, and civil society to foster innovation, while ensuring that the benefits are widely and equally distributed.
Keywords: Fintech; Green finance; Mineral policy; Natural resource consumption; Social globalization; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|